Effect of pre-extraction alkali treatment on the chemical structure and gelling properties of extracted hybrid carrageenan from Chondrus crispus and Ahnfeltiopsis devoniensis - Azevedo, G. (2015)
to investigate the effect of alkali type, concentration and treatment duration on the chemical structure and the gelling properties of extracted hybrid carrageenan (HK). In both seaweeds, increasing the KOH content and the pre-treatment duration gives HK with lower amounts of n-carrageenan units, which have a direct impact on the improved gelling properties. Nevertheless, HK with smaller molecular mass and depressed gel properties are found when excessive KOH content and pre-treatment time are employed. NaOH is more efficient in converting n-carrageenan to i-carrageenan for extracts from C. crispus, whereas NaOH and KOH showed similar results for extracts from A. devoniensis. No correlation between the chemical structure and gel properties was found. A set of HK with 75e80 and 45e50 mol% of k-carrageenan for C. crispus and A. devoniensis, respectively, and tailored gelling properties for a wide range of applications is presented.